Transformasi Pastoral untuk Meningkatkan Partisipasi OMK dalam Sakramen Tobat di Paroki St. Petrus dan Paulus Minomartani, Yogyakarta - Adrianus Musu Sili; Cornelius Satrio Tonapa (Jurnal Penelitian Pendidikan Agama Katolik, 2026)
Participation and Understanding of Catholic Youth in the Sacrament of Penance: A Case Study in St Peter and Paul Minomartani Parish. This study aims to determine the level of participation of Catholic Youth of St Peter and Paul Parish in the service of the Sacrament of Penance. This research uses a quantitative method. The researcher distributed questionnaires in the form of Google Forms containing a series of questions that had been prepared by the researcher to each Catholic Youth of St Peter and Paul Minomartani Parish. The results of this study show that most of the Catholic Youth in St Peter and Paul Minomartani Parish already have a good understanding of the Sacrament of Penance as a means to obtain forgiveness from God. However, despite this understanding, most young Catholics only receive the Sacrament of Penance at certain times, such as during Lent and Advent, or when they are at school or work, where there is an encouragement or opportunity to access this sacrament. This finding indicates the need for a deeper deepening of faith to help the Catholic Youth of St Peter and Paul Parish to appreciate the meaning and importance of the Sacrament of Penance.